Long-term Follow-up of Autosomal Dominant Stargardt Macular Dystrophy (STGD3) Subjects Enrolled in a Fish Oil Supplement Interventional Trial - Choi, Rene (Ophthalmic Genet, 2018)
BACKGROUND: Earlier studies have raised the notion that docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) supplementation could be a useful intervention in autosomal dominant Stargardt macular dystrophy (STGD3). We sought to assess whether fish oil supplementation has a beneficial effect on the clinical course of STGD3 secondary to a mutation in the ELOVL4 gene. MATERIALS AND METHODS: Eleven patients with STGD3 were enrolled in an 8-year open-label, clinical interventional study of over-the-counter fish oil supplements at a recommended daily dose of 650 mg EPA and 350 mg DHA (NCT00420602). Subjects had annual eye examinations with complete imaging, visual function testing and blood lipid analyses. Compliance with therapy was measured by periodic patient self-report and with serum and red blood cell biomarkers of lipid consumption. Paired sample t-tests were used to measure differences in mean values of visual acuity, lipid biomarkers, and contrast sensitivity obtained at baseline and the last follow-up. RESULTS: All subjects showed progression of their maculopathy, and we could not discern a beneficial effect of the intervention. Compliance with the recommended fish oil supplement intervention was poor as assessed by patient self-report and biomarkers of lipid consumption. CONCLUSIONS: Our inability to detect a benefit of fish oil could be the result of small subject numbers, poor compliance, or intervention too late in the course of the disease. We still advise STGD3 patients to consume fish or fish oil regularly, and we recommend that pre-symptomatic children with ELOVL4 mutations should be especially targeted for these interventions.